Éster de sacarose no controle do Varroa estructor em abelhas africanizadas - Castagnino, Guido Laércio; Orsi, Ricardo de Oliveira [UNESP]; Da Cunha Funari, Silvia Regina [UNESP] (Universidade Estadual de Maringa, 2009)
This study aimed to determine the effect of sucrose ester on the control of Varroa destructor mite infestation in Africanized honeybees. For the in vitro experiments, the product was tested in bees and mites at five concentrations obtained through dilution in water (T0: 100% distilled water; T1: 0.5%; T2: 1%; T3: 2%; T4: 5%; and T5: 10% sucrose ester).For the field studies, the experimental design was completely randomized, with four treatments and seven replicates, totaling 28 colonies, from which seven were the controls, seven were treated with 0.1% sucrose ester, seven with 0.2% sucrose ester, and seven hives with 0.5% sucrose ester diluted in water. In the in vitro study, the sucrose ester at 0.5% concentration caused mite and bee mortality. In the field tests, the product at 0.2% concentration reduced Varroa destructor infestation in Africanized honeybees and, therefore, may be used as a tool to control this pest. At 0.1, 0.2, and 0.5% concentrations, sucrose ester did not impair the establishment of open and capped brood areas, as well as stored food areas in the hive, suggesting it is not toxic to Africanized honeybees.
Sucrose ester in the control of Varroa destructor in Africanized honeybees
Keywords: Apis mellifera; Bioacaricide; Mite; Natural product; Acari; Apis mellifera scutellata; Apoidea; Varroa; Varroa destructor